2019
DOI: 10.1186/s12884-019-2181-2
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular injection, intravenous infusion, and intravenous bolus of oxytocin in the third stage of labor for prevention of postpartum hemorrhage: a three-arm randomized control trial

Abstract: BackgroundOxytocin for postpartum hemorrhage (PPH) prophylaxis is commonly administered by either intramuscular (IM) injection or intravenous (IV) infusion with both routes recommended equally and little discussion of potential differences between the two. This trial assesses the effectiveness and safety of 10 IU oxytocin administered as IM injection versus IV infusion and IV bolus during the third stage of labor for PPH prophylaxis.MethodsIn two tertiary level Egyptian maternity hospitals, women delivering va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 32 publications
2
36
0
3
Order By: Relevance
“…A large-scale study conducted in Egypt showed that IV Oxytocin bolus was more effective than IV infusion or IM injections without any significant adverse effects. 4 Other studies have shown that there is less blood loss when Oxytocin bolus is used. However, the adverse effects seen with IV bolus Oxytocin are more with doses of 10 IU or 5 IU.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large-scale study conducted in Egypt showed that IV Oxytocin bolus was more effective than IV infusion or IM injections without any significant adverse effects. 4 Other studies have shown that there is less blood loss when Oxytocin bolus is used. However, the adverse effects seen with IV bolus Oxytocin are more with doses of 10 IU or 5 IU.…”
Section: Discussionmentioning
confidence: 99%
“…20 However, doses of 3 IU have not shown to cause statistically significant hemodynamic changes. 4 Various studies have used higher doses of Oxytocin infusion of 40 IU. 21 This would lead to excessive use of Oxytocin which may be unnecessary and would lead to extra cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Economic issues should also be considered because of a higher carbetocin cost. Moreover, an intravenous administration of oxytocin was shown as more effective (due to severe EPH, blood transfusion and admission to a high dependency unit) than intramuscular administration in the 3 rd stage of labor [33]. Another trial showed acceptable outcomes of misoprostol in comparison with oxytocin, but a high price of misoprostol was emphasized [34].…”
Section: Discussionmentioning
confidence: 99%
“…2 The recommendations are more widely accepted for vaginal delivery; and both IV infusion and IV bolus have been shown to have no safety concerns after vaginal delivery. 3 However, there are concerns about the hemodynamic changes associated with bolus dose of oxytocin during caesarean section. 4 The practice in United States is to use oxytocin infusion alone, whereas the standard practice among the obstetricians and anaesthetists in UK is the use of IV bolus 5-10 U and the Royal college of Obstetricians also recommends 5U I/V oxytocin bolus alone after cord clamping, even though oxytocin has a short half-life of 4-10 minutes.…”
Section: Introductionmentioning
confidence: 99%